Ley orgánica de regulación y control del poder de mercado y su impacto en las prácticas comerciales del sector de bienes de consumo alimenticio en las cadenas de supermercados y sus proveedores de la ciudad de Calceta - Realpe Avellán, Ivana Jacqueline (2020)
The analysis of the Organic Law of Regulation and Control of Market Power and its impact on the commercial practices of the food consumer goods sector in the chains of supermarkets and suppliers in Calceta allowed through the application of research methods: deductive , inductive, analytical, synthetic, statistical and comparative to systemize the information and know the current state of business practices and their relationship with Resolution 014 Regulatory Standards for Supermarket Chains and their Suppliers, we proceeded to collect information related to the study variables itself that was used to elaborate the interview and survey questionnaires that were reviewed by experts in the subject under investigation, the interview with the technicians of the Superintendence of Control and Market Power allowed to know the way in which supermarkets and their suppliers must comply with the provisions of Resolution 014 and cu These are the business practices that occur most frequently, on the other hand, the interviews carried out with the managers or owners of the Tía and Junical supermarkets, as well as the 43 surveys carried out on the suppliers of food consumer products belonging to the Popular Economy and Solidarity reflected the lack of knowledge of Resolution 014. The use of the Ishikawa technique facilitated the grouping of causes and effects related to the unfavorable results detected, for which, through the 5w + 1h matrix, actions to overcome were proposed, thus allowing improvement aspects with insufficient performance. The use of the Ishikawa technique facilitated the grouping of causes and effects related to the unfavorable results detected, for which, through the 5w + 1h matrix, actions to overcome were proposed, allowing improvement of aspects with insufficient performance.